Coating of Ti-6Al-4V Metal Alloys Nanotube with Hydroxyapatite-Gelatin-Polyvinyl Alcohol Composites using the Dip-Coating Methods - Charlena, Charlena; Wahyudi, Setyanto Tri; Nurmawan, Cucu Putri (Chimica et Natura Acta, 2025)
The Ti-6Al-4V metal alloy is an implantable material because of its strength, lightweightness, and corrosion resistance properties. Metal alloy surfaces need to be modified to improve corrosion resistance. Therefore, the study aims to modify the surface of Ti-6Al-4V metal alloys to form nanotube structures and to coat the hydroxyapatite composite (HAp)-gelatin-PVA in Ti-6Al-4V metal alloys. Nanotubes were formed by anodizing methods in an ethylene glycol-H2O (9:1) solution containing 0.6% NH4F at 20V for 3 hours. The result of SEM showed that the diameter of the nanotube hole is about 30−40 nm and that it is formed homogeneously. The result of coating nanotube metal alloys with composite HAp-gelatin-PVA is that they are evenly distributed and thicker. The morphology of a homogeneous small granule composite coating composite. The X-ray diffraction showed shows that the composite HAp-gelatin-PVA crystalline size coated on nanotube metal alloy is smaller than that of non-nanotube. Nanotube Ti-6Al-4V coated metal alloy with HAp-gelatin-PVA composites had shows poor bioactivity that had not beenand thus not able to increase the corrosion resistance of Ti-6Al-4V metal alloys.